Representasi Tubuh Perempuan Dalam Performance Art Karya Melati Suryadarmo - Isnanta, Satriana Didiek (Institut Seni Indoensia Surakarta, 2010)
This article addresses the question of focus related to the struggle for identity (body) of women in the new field called contemporary art, espe-cially in the work of performance art mance. With the consideration that performance art is one of the genre in contemporary art instruction to made deconstruction modern art (fine art) by the road doing demate-rialitation art.By using the body as a medium, the presence of the body in performance art became highly political. Espe-cially the work of performance artist (performer) named Melati Suryadar-mo. Electoral Budget Suryadarmo, because she's a performance artist- international standard and works much voiced about gender, espe-cially on issues of women's bodies in social reality.Works analyzed using Suryadarmo Budget semio when, in particular the